2013
DOI: 10.1063/1.4793562
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of shear banding in amorphous ZrCuAl nanopillars by irradiation

Abstract: Using molecular dynamics simulations, model Zr50Cu40Al10 metallic glass (MG) nanopillars were subjected to simulated irradiation processes followed by uniaxial compression tests. As the intensity or dosage of irradiation increases, the plastic deformation mode of the MG nanopillars transits from localized shear banding to homogeneous shear flow. The suppression of shear banding in MG nanopillars is due to irradiation-induced structural disordering. Furthermore, a correlation is found between the average potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…demonstrate that at high doses of low energy recoils (47.3 eV and 106.4 eV) deformation becomes increasingly homogeneous, as would be expected in rapidly quenched glasses [8]. However, Avchaciov et al simulated deformation of 20 keV irradiated amorphous Cu 64 Zr 36 and found an increase in strain localization in the irradiated alloy [18].…”
Section: Sqz Model and Radiation-induced Ductilizationmentioning
confidence: 95%
See 2 more Smart Citations
“…demonstrate that at high doses of low energy recoils (47.3 eV and 106.4 eV) deformation becomes increasingly homogeneous, as would be expected in rapidly quenched glasses [8]. However, Avchaciov et al simulated deformation of 20 keV irradiated amorphous Cu 64 Zr 36 and found an increase in strain localization in the irradiated alloy [18].…”
Section: Sqz Model and Radiation-induced Ductilizationmentioning
confidence: 95%
“…Previous modeling studies have investigated radiation response in metallic glass compositions, including Ni-P [16], Cu-Ti [7,17], Cu-Zr [8,18] and Cu-Nb [19]. We choose to study amorphous alloys of copper (Cu) and niobium (Nb) (a-Cu x Nb 1Àx ) because their atomic-scale structure has been characterized experimentally [20] and a reliable embedded atom method (EAM) interatomic potential has been constructed to model them [21].…”
Section: Model Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the above contradicting reports in search of the size-dependent cross-over in fl ow behavior all employ FIB for sample preparation, it seems clear that the preparation method may be one of the factors responsible for the apparent "brittle-to-ductile" transition. Further support for this irradiation induced "brittle-to-ductile" transition in small scale systems is given by molecular dynamics (MD) simulations, [ 30 ] where the suppression of shear-banding is explained by irradiation induced atomic scale (re)disordering that is characterized by the average potential energy of the system.…”
Section: Doi: 101002/adma201401123mentioning
confidence: 99%
“…[12,19,25,26] However, TSs have a distinctly different effect on atomic structure evolution in amorphous metals. [27][28][29] By computing voxel-level strains, we find that the material immediately adjacent to TSs undergoes permanent plastic deformation. The tensile work-equivalent plastic strain p of black voxels in Figure 1(c) exceeds 1.25%.…”
mentioning
confidence: 99%